Application of CCD in RSM to obtain optimize treatment of POME using Fenton oxidation process - Saeed, M.O. (Elsevier Ltd, 2015)
Post treatment palm oil mill effluent (POME) is typically non-biodegradable and contains high organic and inorganic matter. This study aims to optimize the operating parameters of the Fenton process in removing recalcitrant organics from POME by using a central composite design (CCD), which is a response surface methodology (RSM) module in the Design-ExpertÂ® software. Important parameters such as reaction time, H2O2 and Fe2+ ion concentrations, and pH were empirically determined and successfully optimized via RSM. Significant statistical quadratic polynomial for color and COD removal efficiency were obtained via regression analyses R2, (0.81 and 0.70) for color and COD, respectively. The highest results were 97.36 removal for color and 91.11 removal for COD at pH 3.5 and 30min of reaction time. Numerical optimization based on desirable functions was employed; 92.1 of color and 85.1 of COD were removed efficiently at pH (3.0-5.0) with a final pH of 2.85 (after reaction settlement), 4.57g/L H2O2 and 1.88g/L Fe2+ ions concentration, respectively, and 30min of reaction time at 120rpm agitation rate. The result showed that the Fenton process, at an accurate level, may be used as an effective technology for the post treatment of POME before final discharge into a nearby water body. Â© 2014 Elsevier Ltd.